Multiple intelligences among educational counselors in Jordanian schools and their relationship to gender and academic qualifications - Al-Khamaiseh, Omar Soud (Journal of Education and e-Learning Research, 2025)
This study aimed to identify the nature of multiple intelligences among educational counselors in Jordanian schools by examining the predictive differences in multiple intelligences among educational counselors, as well as their relationships and impacts based on demographic variables, gender, and academic qualifications. The researcher developed the Multiple Intelligences Scale for Educational Counselors, which was utilized in the study, adopting a descriptive analytical methodology. The results indicated that the level of multiple intelligences among the sample members was average. No statistically significant differences were found in multiple intelligences based on gender. Additionally, there were no significant differences according to educational qualifications, except for existential intelligence, which was higher among those with a doctorate degree in multiple intelligences. Finally, a set of recommendations was proposed based on the incoming results, emphasizing the importance of conducting similar future studies and the need for continuous training, qualification, and development programs to activate multiple intelligences among the members of the study sample in the provision of educational counseling services.